Combined treatment with chlorhexidine and 0.9% saline in a newborn infant with an infected surgical wound - KEPENEKLİ KADAYİFCİ, EDA (WILEY-BLACKWELL, 2016)
Newborns are more susceptible to infection; this makes proper wound care extremely important in them. Unfortunately, in spite of successful surgery, patients can die as a result of wound area infections. Herein, we report a case in which a combined therapy of chlorhexidine (a disinfectant) and saline (a cleansing agent used in wound care) was used effectively to treat the wound in a newborn infant with an antibiotic-resistant, Gram-negative, bacteria-related surgical site infection.
Keywords: Infection; Meningomyelocele; Newborns; Wound; RANDOMIZED CONTROLLED-TRIAL; POVIDONE-IODINE; NEONATAL-MORTALITY; SOUTHERN NEPAL; CONTAMINATION; IMPACT